A study on enhancing EFL students vocabulary proficiency via TikTok - Muhammad Usman; Marisa Yoestara; Muhammad Rizal; Cut Nurjannah; Noorul Azra Mohamed (Universitas Syiah Kuala, 2024)
TikTok can be used for many purposes, including for mastering English vocabulary. This study aims to determine the improvement of EFL students English vocabulary ability after being taught vocabulary using TikTok videos. This study used a quasi-experimental design with a total of 178 Grade VII EFL students from a state junior high school in northern Sumatra. In this study, the sample consisted of two groups, totaling 61 students, which were then divided into two groups: the experimental group and control group. In collecting the data, the researchers conducted vocabulary tests in both the pre- and post-tests. The results revealed that the students average pre-test score in the experimental group was 66.44, while the average of the students pre-test scores in the control group was 65.77, indicating similar initial achievements. However, the mean post-test score of the experimental group after being taught vocabulary using TikTok videos remarkably increased to 91.39, while the mean post-test score of the control group was 79.99. Furthermore, the SPSS result also showed that the t-score of the post-test in the experimental and control groups was 5.83, at the 5% level of significance (= 0.05), which was out of the limits of 1.96 and 1.96. Therefore, the acceptance of the alternative hypothesis suggests that teaching vocabulary through the TikTok application has a significant positive impact on vocabulary proficiency. Therefore, EFL teachers are encouraged to selectively incorporate TikTok videos into their vocabulary teaching approaches.